Aquaculture entry barriers for farmers in Odisha – Focus Group Discussion Protocols and Outputs - Dam Lam, Rodolfo (2023)
This dataset ptovides the transcripts of each focus group discussion and consolidated response sheet with farmers in Odisha. Participant selection protocols, consent form, FGD primary and probing questions, and response sheet template is also available.